Perancangan Aplikasi Surat Menyurat Berbasis Web di Kantor Desa: Studi Kasus Desa Amboyo Selatan - Agustinus, Agustinus; Astuti, Femi Dwi (IAI Nasional Laa Roiba Bogor, 2025)
This research aims to design and develop a web-based correspondence application to improve the efficiency and effectiveness of the correspondence process at the South Amboyo Village Office. This research uses the research and development method with the stages of analyzing the needs for the system designed, and evaluated. Data was collected through interviews, observations, and questionnaires, and analyzed descriptively qualitative and quantitative. The application provides features such as incoming and outgoing mail management, letter creation, letter disposition, letter archiving, and reporting. System evaluation shows that this application has good performance, easy to use, and secure. This research contributes to the development of correspondence applications in village offices and can be a reference for further research.